2021
DOI: 10.3390/polym13142262
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnological Manipulation of Nutraceuticals and Phytochemicals for Healthy Purposes: Established Advantages vs. Still Undefined Risks

Abstract: Numerous foods, plants, and their bioactive constituents (BACs), named nutraceuticals and phytochemicals by experts, have shown many beneficial effects including antifungal, antiviral, anti-inflammatory, antibacterial, antiulcer, anti-cholesterol, hypoglycemic, immunomodulatory, and antioxidant activities. Producers, consumers, and the market of food- and plant-related compounds are increasingly attracted by health-promoting foods and plants, thus requiring a wider and more fruitful exploitation of the healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 174 publications
0
30
0
Order By: Relevance
“…Nanotechnology has been applied both to deliver compounds with health properties and to produce nanoparticles using food-derived materials, also called "nanoceutical materials", for embedding compounds with beneficial activities on human health. Consumers' increasing interest and trust in natural health products have boosted this scientific research in recent decades, as previously reported [6]. Nutraceuticals are essential nutrients for human health and well-being and are present in edible food products.…”
Section: Introductionmentioning
confidence: 93%
“…Nanotechnology has been applied both to deliver compounds with health properties and to produce nanoparticles using food-derived materials, also called "nanoceutical materials", for embedding compounds with beneficial activities on human health. Consumers' increasing interest and trust in natural health products have boosted this scientific research in recent decades, as previously reported [6]. Nutraceuticals are essential nutrients for human health and well-being and are present in edible food products.…”
Section: Introductionmentioning
confidence: 93%
“…Epidemiological studies have evidenced that the ingestion of some foods, including edible plants, is associated with the onset of beneficial health effects. An example is the assumption that red wine is correlated with a decrease in death from cardiovascular events caused by atherothrombosis due to its capability of decreasing the progression of atherosclerotic lesions [ 1 ]. Additionally, it has been demonstrated that green vegetables exert protective effects against cardiac diseases [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…An example is the assumption that red wine is correlated with a decrease in death from cardiovascular events caused by atherothrombosis due to its capability of decreasing the progression of atherosclerotic lesions [ 1 ]. Additionally, it has been demonstrated that green vegetables exert protective effects against cardiac diseases [ 1 ]. The bioactive chemical compounds responsible for these benefits are known as phytochemicals (PHYs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, despite being active, a possible clinical application of the insoluble free form of BBB4 would remain utopian unless water-soluble BBB4 formulations were developed. To address the problems related to the solubility of bioactive compounds, several nanotechnological strategies have provided very promising results [ 23 , 24 , 25 ]. In this field, due to their nonpareil physicochemical properties, dendrimers are extensively applicated [ 24 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%